Relationship between gastritis history, age and parity with the incidence of hyperemesis gravidarum in pregnant women at the Main Mariani clinic, Medan Petisah district, Medan city in 2022 - Suhartini, Suhartini; Sari, Juita (Sean Institute, 2024)
The exact cause of Hyperemesis gravidarum is not yet known, but the complex interaction of biological, psychological and socio-cultural factors of multiple pregnancies, women with their first pregnancy, ages <20 years and >35 years, molar pregnancies, excess body weight is thought to be the cause of Hyperemesis gravidarum (Anasari, 2020). From the results of Basic Health Research (RISKESDAS) in 2020 there were 13.1% of pregnant women with Hyperemesis gravidarum with almost the same proportion in urban areas (36.4%) and rural areas (37.8%). The purpose of this study was to determine the history of gastritis, age and parity with the incidence of hyperemesis gravidarum in pregnant women at the Main Mariani Clinic, Medan Petisah District, Medan City in 2022. This type of research uses quantitative research with descriptive correlation research methods in order to determine the relationship between the independent variables and the dependent variables. Survey research design using an analytic cross sectional approach. Where researchers make observations or measurements of variables at one time and the time used is retrospective. The population and sample are 42 people, the sampling technique is total sampling. The data collected in this study were secondary data, namely data obtained from the medical records of Mariani's main clinic. The data analysis used was univariate analysis and bivariate analysis using Fisher's Exact Test. Based on statistical results using the Fizher's Exact Test, it shows that there is a relationship between a history of gastritis and the incidence of hyperemesis gravidarum, a p value of 0.002 <0.05. There is no relationship between age and the incidence of hyperemesis gravidarum with a p value of 1.00 > 0.05. There is no relationship between parity and the incidence of hyperemesis gravidarum with a p value of 0.749 > 0.05). The conclusion in this study is that the age factor is that the majority of ages are not at risk and parity is multipara, this causes no relationship. It is hoped that all health workers are expected to be more active in providing services and improving health for pregnant women.